2020
DOI: 10.1186/s12904-020-00690-2
|View full text |Cite
|
Sign up to set email alerts
|

A non-lab nomogram of survival prediction in home hospice care patients with gastrointestinal cancer

Abstract: Background Patients suffering from gastrointestinal cancer comprise a large group receiving home hospice care in China, however, little is known about the prediction of their survival time. This study aimed to develop a gastrointestinal cancer-specific non-lab nomogram predicting survival time in home-based hospice. Methods We retrospectively studied the patients with gastrointestinal cancer from a home-based hospice between 2008 and 2018. General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The prognosis demonstrated in the current study, of elderly patients hospitalized for acute illness in internal medicine wards and fed with NGT, was similar to that reported among patients with terminal cancer. 21 , 22 The poor prognosis of our patients may prompt questions regarding the initiation of NGT feeding. Possibly, some of our patients could have been better managed by assisted hand feeding or other palliative treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The prognosis demonstrated in the current study, of elderly patients hospitalized for acute illness in internal medicine wards and fed with NGT, was similar to that reported among patients with terminal cancer. 21 , 22 The poor prognosis of our patients may prompt questions regarding the initiation of NGT feeding. Possibly, some of our patients could have been better managed by assisted hand feeding or other palliative treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Plyta et al (2020) explored the relationship between nutritional status and quality of life of hospitalized cancer patients with intestinal failure and need parenteral nutrition and found that KPS, which is impaired by muscle strength, was the main component of QoL damage in patients. In addition, Wang et al (2020) found that physical status can improve survival predictions in patients with advanced gastrointestinal cancer. Therefore, healthcare providers and caregivers are encouraged to pay attention to the level of self‐care ability of patients, which can not only help to evaluate the overall functional status of patients but also reflect the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health technology has been widely adopted in end-of-life care for various purposes, such as education, telemedicine, and prognosis prediction using electronic health records [24][25][26][27][28][29][30][31]. Although wearable devices have also been demonstrated to help monitor and predict physical conditions [32][33][34][35][36][37][38][39][40], there have been only a few studies on the use of wearable devices in end-of-life care.…”
Section: The Application Of Wearable Devices and Artificial Intellige...mentioning
confidence: 99%